Behavioral Investigation of the Influence of Social Categorization on Empathy for Pain: A Minimal Group Paradigm Study - Montalan, Benoit; Lelard, Thierry; Godefroy, Olivier; Mouras, Harold (Frontiers in Psychology, 2012)
Research on empathy for pain has provided evidence of an empathic bias toward racial ingroup members. In this study, we used for the first time the “minimal group paradigm” in which participants were assigned to artificial groups and required to perform pain judgments of pictures of hands and feet in painful or non-painful situations from self, ingroup and outgroup-perspectives. Findings showed that the mere categorization of people into two distinct arbitrary social groups appears to be sufficient to elicit an ingroup bias in empathy for pain.